Toxicological effects caused by environmental relevant concentrations of ketoconazole in Chironomus sancticaroli (Diptera, Chironomidae) larvae evaluated by oxidative stress biomarkers - do Prado, Caio César Achiles; Queiroz, Lucas Gonçalves; da Silva, Flávio Teixeira; de Paiva, Teresa Cristina Brazil (Comparative biochemistry and physiology. Toxicology & pharmacology, 2023)
Ketoconazole (KTZ), a broad-spectrum fungicidal drug, has been a significant problem in recent decades due to its toxic action on non-target aquatic organisms. Thus, the present study aimed to evaluate determine the effects that environmental relevant concentration of the commercial formulation of KTZ can exert on benthic macroinvertebrates, more specifically on larvae of the insect Chironomus sancticaroli. Acute toxicity tests with KTZ indicated lethal concentration (LC50) of 9.9 μg/L. Analyses of prolonged exposure to KTZ (chronic toxicity) indicated an increase in the rate of mentum deformity by approximately 3 times at concentrations of 0.6 and 2.4 μg/L. All biomarkers analyzed showed an increase after exposure to KTZ (0.6 and 2.4 μg/L), with average values of 115 % for superoxide dismutase (SOD), 63 % for catalase (CAT), 111 % for glutathione S-transferase (GST) and 59 % for malonaldehyde (MDA) in C. sancticaroli larvae. Thus, the toxic effects on survival, development (length and weight), mentum and redox responses caused by commercial KTZ in low concentrations were observed on C. sancticaroli larvae. In addition, the results suggest that biochemical biomarkers can be used for studies involving environmental disturbances. [Display omitted] •Environmental relevant concentrations of ketoconazole are toxic to chironomids.•C. sancticaroli showed acute toxicity from the concentration of 1.4 μg/L of KTZ.•KTZ (<0.6 μg/L) causes modifications on survival and development of C. sancticaroli.•Commercial KTZ (0.6 and 2.4 μg/L) promoted an oxidative stress on C. sancticaroli.•SOD, CAT, GST and MDA biomarkers show complement to KTZ toxicology responses.